Knowing One's Place: Loyal Servitude as a Key Aspect of a Good Ruler according to the Book of Judith - Korytiaková, Martina (Orientalia, 2024)
This study shows that, according to the book of Judith, a good ruler should primarily be an embodiment of servitude and loyalty to God. God is the only sovereign who fits the criteria for an ideal Hellenistic ruler and even surpasses them. Any political leader of the Jews should keep his/her second ranked position to God and avoid reversal of roles in the hierarchy of power. Judith’s temporary leadership functions as the so-called Princes’ mirror held up to the national Jewish rulers, showing them their failure in ministry. By their concept of rulership marked by loyal servitude to God as demonstrated in Judith’s ad hoc leadership, the Jews distinguish themselves from the Gentiles, whose kings claim divine status for themselves but are nevertheless betrayed by their disloyal servants, who have no scruples about replacing them. The paper proposes that the image of a Jewish ruler communicated by the book of Judith may indicate a pro-Hasmonean orientation instead of an anti-Hasmonean critique.